DIAGNOSTIC BRONCHOSCOPY IN CHILDREN - A. Yu. Kharitonova; A. A. Shavrov; N. A. Kalashnikova; A. A. Shavrov (Jr.) (Вопросы современной педиатрии, 2013)
In recent years there has been significant progress in pediatrics, including pediatric pulmonology and endoscopy, which led to marked achievements in diagnostics, treatment and prophylaxis of respiratory tract disorders in children. The wide spectrum of various questions of anatomical and physiological peculiarities of the children respiratory tract is discussed in this article. The authors give a systematical review of indications and contraindications for bronchoscopy and offer the algorithm of choice of the optimal and most informative method of investigation. The modern conceptions of preparation and anesthesia methods for the bronchoscopic procedures in children are shown. The importance of complex analysis of the revealed during bronchoscopy structural and functional disorders of the respiratory tract depending on the nosological issue and characteristics of the disease clinical course is accentuated. The article contains descriptions of endoscopic patterns of the most common trachea and bronchi abnormalities in children, as well as detailed techniques of the bronchoalveolar lavage, forceps and brush-biopsy. The unique original data on newest endoscopy method — confocal laser endomicroscopy (alveoscopy) in older children, which had never previously used before neither in the Russian Federation, nor in the other countries, are of the most interest. The article is illustrated by demonstrative endoscopic images.